Deskripsi Morfologi dan Biomassa Bibit Kelapa Sawit (Elaeis guineensis Jacq.) dengan Penambahan Amelioran Kompos Eceng Gondok pada Media Tumbuh Subsoil - Sylvia Madusari; Toto Suryanto; . Sa'dun; Saiful Hidayat (Politeknik Kelapa Sawit Citra Widya Edukasi, 2019)
Water hyacinth is an invasive plant that often causes a decrease in environmental quality. Water hyacinth composts were done by chopping water hyacinth and mixing the chopped with cow dung with a ratio of 3: 1, and commercial bioactivators. The study was conducted in two groups of oil palm seedlings and each group consisted of 5 treatments The first group consisted of P10 = 100% subsoil, P11 = 100% water hyacinth compost, P12 = subsoil and sand + water hyacinth compost (3:1), P13 = subsoil and sand + water hyacinth compost (1:1), P14 = subsoil and sand + water hyacinth compost (1:3). The second group consists of P20 = 100% subsoil, P21 = 100 water hyacinth compost, P22 = subsoil + water hyacinth compost (3:1), P23 = subsoil + water hyacinth (1:1), P24 = subsoil + water hyacinth compost (1:3). The results of the study on group one of palm oil seedlings showed that 25% subsoil and sand planting media + 75% water hyacinth compost gave the highest plant growth at 3 BST. Group two plants showed that the application of water hyacinth compost on the planting medium had a significant effect on plant height successively in the treatment P23 = 50% subsoil + 50% water hyacinth (22.5 cm). Invasive water hyacinth potentialy to be used as an alternative mixture of growing media for crop cultivation.